Lintang and the pirate queen - Moss, Tamara (Clarion Books, 2022)
Lintang's dream of adventure on the high seas comes true when Captain Shafira invites her to join her pirate crew, but Lintang's best friend, Bayani, has stowed away and is keeping secrets.